Regioselective and diastereoselective iodocyclization reaction of alkene-thioureas: an efficient approach to bicyclic beta-lactams - Garud, Dinesh R.; Sonawane, Amol D.; Auti, Jyoti B.; Rode, Navnath D.; Ranpise, Vinod R.; Joshi, Rohini R.; Joshi, Ramesh A. (New Journal of Chemistry, 2015)
Bicyclic beta-lactams, i.e. 3-thia-1-dethiacephams, were synthesized via a highly regioselective and diastereoselective iodocyclization reaction of alkene-thioureas with molecular iodine. Furthermore, the structure of 3-thia-1-dethiacepham was confirmed by a chemical method, the dehydrohalogenation reaction using DBU.